2017
DOI: 10.1515/acb-2017-0008
|View full text |Cite
|
Sign up to set email alerts
|

Fat graft – the natural choice for reconstructive, regenerative and aesthetic surgery

Abstract: The search for appropriate filler, which can be used for aesthetic and reconstructive operations is currently one of challenges for plastic surgery. The application of absorbable and permanent artificial fillers may cause adverse events. Thus, autologous fat grafting can be a safe alternative. Moreover, fat tissue is rich in adipose-derived stem cells (ASC), which can be successfully used for regenerative procedures. The paper reviews reports on fat grafting procedures, which indicate risks and their possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…18 Ibrahim et al suggested that fat graft are the natural choice for reconstructive, regenerative and aesthetic surgery but long term studies are needed to assess the stability of the breast after fat grafting found better survival of fat harvested from thighs. 19 This study evaluated volume loss with ultrasonography and we compared two most commonly used sites as a donor of fat cells i.e. thigh and abdomen to check the preoperative and postoperative thickness of subcutaneous tissue.…”
Section: Discussionmentioning
confidence: 99%
“…18 Ibrahim et al suggested that fat graft are the natural choice for reconstructive, regenerative and aesthetic surgery but long term studies are needed to assess the stability of the breast after fat grafting found better survival of fat harvested from thighs. 19 This study evaluated volume loss with ultrasonography and we compared two most commonly used sites as a donor of fat cells i.e. thigh and abdomen to check the preoperative and postoperative thickness of subcutaneous tissue.…”
Section: Discussionmentioning
confidence: 99%